Matlab by example : programming basics - Gdeisat, Munther; Lilley, Francis (Elsevier insights., 2013)
This book is designed to guide the reader through each step of writing Matlab programs. The book begins assuming the reader has no previous programming experience, and it uses multiple examples and clear language to introduce concepts and practical tools. The straight-forward and detailed instructions provide quick and thorough learning of Matlab for the beginner, allowing them to improve quickly in a short time. The book consists of ten parts and it discusses in detail the integrated development environment (IDE), scalars, vectors, arrays, adopting structured programming style using functions.